Insect diversity and guild composition in seasonal tropical fruit orchards (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Tropical seasonal fruit orchards are dynamic ecosystems that support a wide range of insect species, contributing significantly to regional biodiversity and various ecological functions. This study aims to assess the diversity and guild structure of insects in fruit orchards in Northern Malaysia during both the off-season (December 2022–January 2023) and the flowering season (February 2023 – April 2023). Insects were collected using pheromone traps, malaise traps, and sticky traps across four locations in Penang and Kedah, Malaysia. A total of 1,930 individual insects, representing 11 orders and 56 families, were captured during the off-season, while 4,569 individuals from 11 orders and 58 families were recorded during the flowering season. Chrysopidae (Neuroptera) was the most abundant family during the off-season (688 individuals), whereas Tephritidae (Diptera) dominated the flowering season (1,863 individuals). The flowering season exhibited greater insect diversity (H’=2.134) and evenness (E=0.526), although the off-season had higher species richness (IMargalef = 7.27). In terms of guild structure, pests were the dominant insect guild in both seasons, followed by pollinators. By comparing the relative abundance across the two seasons, pest abundance increased from the off-season to the flowering season, while pollinator abundance significantly decreased. This finding provides valuable insights into the insect fauna within the fruit orchards which can contribute to a better understanding of insect ecology and aid in the development of sustainable pest management strategies.
Keywords: flowering season; insects; pest; pollinator; off-season